Management of Teacher Education and Training Centers in West Java - N. Ela Nurlaela; Yusuf (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The management of the Education center and teacher training have a central role in improving the quality of Education personnel. In West Java, this center is key in organizing teacher development programs. This study aims to investigate the management of teacher education and training centers in West Java, focusing on aspects of personnel, financing, facilities and infrastructure, and community relations. This study uses a literacy study method by detailing literature related to education and training center management. Information is collected from scientific articles, books, and official documents related to Education in West Java. The findings show challenges in personnel management, especially related to the selection and development of human resources. Financing is becoming a critical issue, with expanding funding sources and optimizing fund allocation considered crucial. The management of facilities and infrastructure is found to require innovation, especially in integrating technology into the learning process. Public relations management also requires more attention to ensure broad support from the community. This research provides in-depth insights into the management of teacher education and training centers in West Java. The implications of the findings can be used as a foundation for developing more effective policies in improving the quality of education and teacher training, fiber makes a positive contribution to the development of education at the regional level.